Menggunakan Studi Kasus sebagai Metode Ilmiah dalam Psikologi - Unika Prihatsanti; Suryanto Suryanto; Wiwin Hendriani (Buletin Psikologi, 2018)
As a research method, case studies are often used in qualitative research, but there is no agreement on research procedures. Case studies have been widely used in psychology, which is not only used in the context of research but it has different meanings. The purpose of this article is to provide a description of the case study as a research method, by providing an overview of the procedures for conducting research which includes when case studies can be used, research design, data collection, data validity, and data analysis. This article seeks to help emerging researchers in the field of psychology with several views from Robert Yin and Robert Stake. This article helps researchers to familiarize themselves with the procedures of qualitative research using case studies. A case study approach that is applied correctly can be a valuable method for conducting research, especially in the field of psychology as a means of developing theory, evaluating programs, developing interventions.